2007
DOI: 10.1002/mame.200700019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of PP Nano‐ and Microcomposites by In‐Mold Shrinkage Measurements and Structural Characteristics

Abstract: Poly(propylene)‐clay nanocomposites and poly(propylene) containing conventional inorganic fillers such as calcium carbonate (CaCO3) and glass fiber were used in a comparative study focusing on dimensional stability, structure, mechanical and thermal properties. Micro‐ and nanocomposites were prepared by melt blending in a twin‐screw extruder. The relative influence of each filler was observed from dimensional stability measurements and structural analysis by WAXD, TEM, and thermal and mechanical properties. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Figure 1c is provided to illustrate the nonisothermal crystallization and melting curves of neat IMPP, neat coupling agents, IMPP/PP-g-MA blends and coupled xGnP 5 -filled IMPP composites at 2 and 4 wt% xGnP. It was reported that PP-g-MA acts as a nucleation agent that can increase crystallization parameters of PP homopolymer [29,30]. Clearly, the experimentally determined values of DH m , DH c , and X c of the two coupling agents are higher than neat IMPP and IMPP/PP-g-MA blends.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Figure 1c is provided to illustrate the nonisothermal crystallization and melting curves of neat IMPP, neat coupling agents, IMPP/PP-g-MA blends and coupled xGnP 5 -filled IMPP composites at 2 and 4 wt% xGnP. It was reported that PP-g-MA acts as a nucleation agent that can increase crystallization parameters of PP homopolymer [29,30]. Clearly, the experimentally determined values of DH m , DH c , and X c of the two coupling agents are higher than neat IMPP and IMPP/PP-g-MA blends.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Several studies on polymer/clay nanocomposites have reported similar results in the thermal properties. Incorporation of nanoclay resulted in a significant improvement on thermal stability of polystyrene, polyvinyl alcohol, PP–EP/EVA and PP …”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of nanoclay resulted in a significant improvement on thermal stability of polystyrene, 31 polyvinyl alcohol, 32 PP-EP/EVA 33 and PP. 34 The increase of the thermal stability for PPR/clay and PPR/PβP/clay samples could be attributed to the clay particles that act as barrier to the diffusion of gases, originated by the thermal degradation process, from the bulk to the surface of the film, contributing to slow the degradation process of the PPR. 35 The increase of the thermal stability for PPR/PβP could be probably due to the double bond present in each unit of the PβP formula.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…As a kind of polar inorganic fillers, the glass fiber (GF) has the most obvious effect on decreasing the PP shrinkage among the inorganic fillers, which does not shrink and has the advantages of high elastic modulus, high strength, stable size, high thermal deformation temperature, good electrical properties, low price, etc . Rodolfo Revilla‐Díaz et al . studied the effect of nano‐clay, calcium carbonate, and GF on PP shrinkage.…”
Section: Introductionmentioning
confidence: 99%